1979
DOI: 10.1902/jop.1979.50.6.279
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Female Sex‐Hormone Levels and Gingivitis in Pregnancy

Abstract: This investigation has confirmed that there is an increase in gingival inflammation between the 14th and 30th weeks of pregnancy and that this will occur despite a fall in the amount of plaque at the dento-gingival junction. This implicates a further factor in addition to plaque accumulation to explain the increased inflammmation. It was confirmed that there are marked increases in the plasma levels of estradiol and progesterone between the 14th and 30th weeks of pregnancy but it was not possible to demonstrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
30
1
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 13 publications
4
30
1
1
Order By: Relevance
“…These results differ from those obtained in humans where pregnancy gingivitis seems to be induced by variations in physiological factors [9,10,25]. It should be noted, however, that gingivitis is generally attributed to the proliferation of strict anaerobes in the human oral bacterial biota [20] and that the mouse does not harbor such anaerobic species [31].…”
Section: Discussioncontrasting
confidence: 59%
“…These results differ from those obtained in humans where pregnancy gingivitis seems to be induced by variations in physiological factors [9,10,25]. It should be noted, however, that gingivitis is generally attributed to the proliferation of strict anaerobes in the human oral bacterial biota [20] and that the mouse does not harbor such anaerobic species [31].…”
Section: Discussioncontrasting
confidence: 59%
“…We have already reported that there is a higher proportion of E.faecalis on the teeth in mice as compared to other sites in the mouth [27]. It is well known that, in humans, puberty is characterized by important hormonal changes and that some of these hormones can be found in the crevicular fluid [10] and saliva [20]. It has been established that these hormones could be used as growth factors by members of the subgingival bacterial flora such as Prevotella intermedia [10,11,15].…”
Section: Discussionmentioning
confidence: 99%
“…17 Some have suggested that pregnancy gingivitis may be an accentuated inflammatory response to dental plaque. 17 Some have suggested that pregnancy gingivitis may be an accentuated inflammatory response to dental plaque.…”
mentioning
confidence: 99%